Challenges Encountered by Junior High School Graduates of the School of Tomorrow Program to Senior High School Program in Capiz: A Case Study - Panaligan, Jan April; Maming, Jimmy Bernabe (Future Science / FSH-PH Publications, 2021)
The School of Tomorrow (S.O.T.) having the Accelerated Christian Education (A.C.E.) here in the Philippines promises that they can give the most advanced twenty-first-century educational system available, but the experiences and grievances of S.O.T. graduates stated otherwise. This case study intends to determine the key informant's experiences in transitioning from Accelerated Christian Education (A.C.E.) institution to conventional schools in Capiz. This study utilized interviews, observation, and data reviews in gathering the data while the Mayring (2002) approach was utilized in analyzing the data. Themes came out from the constructs of the interviewees in Capiz, like S.O.T. curriculum is offered in Pre-School to Junior High School only, difficulty in transitioning from S.O.T. school to conventional schools offering Senior High School Program and conventional schools must be adopted and integrated to the S.O.T. Junior High School. The output of the research is the proposed new S.O.T. curriculum model to help address the existing problems